Catalytic Asymmetric CN Bond Formation: Phosphine‐Catalyzed Intra‐ and Intermolecular γ‐Addition of Nitrogen Nucleophiles to Allenoates and Alkynoates1. Issue 9 (21st January 2013) - Lundgren, Rylan J.; Wilsily, Ashraf; Marion, Nicolas; Ma, Cong; Chung, Ying Kit; Fu, Gregory C.
<x xml:space="preserve">Abstract</x> Pin the amine on the gamma: A new method has been developed for the γ‐addition of nitrogen nucleophiles to γ‐substituted alkynoates or allenoates through intra‐ and intermolecular processes that are catalyzed by spirophosphine 1 (see scheme). An asymmetric version of this reaction affords enantioenriched pyrrolidines, indolines, and γ‐amino‐α, β‐unsaturated carbonyl compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>